Service Quality in Community Based Day Care(PAWE) for Older People in Selangor - Johani, Sarin (International Journal of Psychosocial Rehabilitation, 2020)
This study was conducted to examine the difference of service quality at rural and urban area of PAWE in Selangor. This study also aimed to identify whether there are difference among expectation score and perception score in service quality of PAWE. This quantitative study was conducted using instrument of Service Quality (SERVQUAL). Sample of study were selected by using purposive sampling which include active elderly aged 60 years or above, can independently take care of themselves and have been using services in PAWE for at least three months. There are 156 respondents involved in this study which are from PAWE Sungai Buloh, PAWE Cheras, PAWE Jenjarom and PAWE Sabak Bernam. Result showed that there is no significant difference between service qualities of PAWE in rural or urban areas. There is negative value gap in all five dimensions of service quality which are tangible, reliability, responsive, assurance and empathy. This study also found that there is gap between expectation and perception scores. This showed that service quality in PAWE is still a way below the expectations of elderly. The research resulted in understanding the importance of service quality in institution to ensure the effectiveness of the services offered. This study has implication in Malaysian social work field especially in aspect of planning and improvement of elderly services, as preparation to be Aged Country by 2030.